RETRACTED: Factors and models of economic security of industrial enterprises in a depressed region in the context of digital transformation - Babkin Aleksandr; Shkarupeta Elena; Igolkin Sergey; Rodionova Valentina; Shchegoleva Tatiana; Antonov Ilya (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001